Digital Supply Chain Model for Revenue Collection Management for the Excise Department in Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2023)
The objective of this research   were to study  and to evaluate digital supply chain model for Revenue Collection of the Excise Department in Thailand. The samples in the research study consisted of ten purposively selected experts consisted of five experts on supply chain management, five experts on Digital Technology, Data were analysed by arithmetic mean and standard deviation. The research findings model five elements namely main components, Supplier,   the excise department, and Customers and  Return. The ten experts agree that digital supply chain model for Revenue Collection of the Excise Department in Thailand was high suitability that show the model is appropriate and can be appropriately applied in actual work settings.